Separation and Recovery of Iron and Rare Earth from Bayan Obo Tailings by Magnetizing Roasting and (NH4)2SO4 Activation Roasting - Yan Zhou; He Yang; Xiang-xin Xue; Shuai Yuan (Metals, 2017)
A novel approach for recovery of iron and rare earth elements (REEs) from Bayan Obo tailings of Baotou, China, was developed by combining magnetizing roasting, magnetic separation, (NH4)2SO4 activation roasting, and water leaching. Thermodynamic analysis of carbothermal reduction was conducted to determine the temperature of magnetizing roasting, and it agreed well with the experimental results. The maximum recovery of Fe reached 77.8% at 600 °C, and the grade of total Fe in the magnetic concentrate was 56.3 wt. %. An innovative approach, using water to leach REEs after (NH4)2SO4 activation roasting, was used to extract REEs from magnetic separation tailings. The main influence factors of the leaching recovery during (NH4)2SO4 activation roasting, were investigated with the mass ratio of (NH4)2SO4 to magnetic separation tailings, roasting temperature and roasting time. The leaching recoveries of La, Ce and Nd reached 83.12%, 76.64% and 77.35%, respectively, under the optimized conditions: a mass ratio of 6:1, a roasting temperature of 400 °C and a roasting time of 80 min. Furthermore, the phase composition and reaction process during the (NH4)2SO4 activation roasting were analyzed with X-ray diffraction (XRD), energy dispersive X-ray spectroscopy & scanning electron microscopy (EDS-SEM) and thermogravimetry & differential scanning calorimetry (TG-DSC), and the leaching solution and leaching residue were also characterized.